A very reasonable objective still beyond our reach: Economics as an empirically disciplined social science - Giovanni Dosi (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2002)
The paper discusses some fundamental features of the 'Simonian' research program in microeconomics and compare them with two streams of thought which find their roots into Simon's pathbreaking work since the '50s and '60s, namely Transaction Cost Economics and Evolutionary Economics. One argues that the latter is in a particularly promising position to advance toward the kind of empirically disciplined microeconomics advocated by Herbert Simon. It does so also through painstaking attempts to operationalize the notion of 'bounded rationality' - in the broadest sense -, to make bridges with the microevidence from other social sciences - e.g. cognitive and social psychology, etc. -, and to open up the organizational blackbox. And all that is undertaken outside the straightjacket of any religious committment to equilibrium analysis.
Keywords: 330; Herbert Simon; Evolutionary Economics; Transaction Cost Economics; Bounded Rationality; Organization; Evolutionsökonomik; Transaktionskosten; Beschränkte Rationalität